THE INFLUENCE OF STUDYING MOTIVATION, READING INTEREST AND FATIGUE TO THE ENGLISH STUDYING RESULT FOR THE CADETS OF SEMARANG MERCHANT MARINE POLYTECHNIC (Study at Of Semarang Merchant Marine Polytechnic) - Sri Suyanti, 12.52.02.0183 (Jurnal Mahasiswa Pasca Sarjana, 2015)
This Research have a purpose to explain the influence studying motovation, reading interest and fatigue to the English studying aresult for the cadets of SemarangMerchantMarine Polytechnic. The independent variables are studying motivation, studying interest and fatigue whereas studying result as a dependent variable. Research population are the cadetsof Semarang Merchant Marine Polytechnic, whilesample use the technique of purposive sampling. Method  data collecting by using questionerwhich   passed to a responder. Examination to research instrument done with the validity test (analyse the factor) and test the reliabilitas with the coefficient alpha of appliance to statistic testby multiple regression analysis regresi, test the t, test  R2 and  mediation test.Result of research indicate that studying motivation has a positive effect  to the English studying result, this research show that the higher studying motivation will be able to make the studying result to be high. Reading interest has a positive effect to the English studying result. The research show that the higher reading interest will be able tio make the studying result to be high. Fatigue has a negative effect to the English  studying result. Keyword :Studying Motivation, Reading Interest, Fatigue and Studying Result